Examining heterogeneity of obsessive-compulsive disorder: Evidence for subgroups based on motivations. (January 2017) - Bragdon, Laura B.; Coles, Meredith E.
Highlights: A model of OCD based on levels and types of motivations is supported. A traditional OCD group marked by high motivation to avoid harm and beliefs about responsibility/overestimation of threat was identified. A second group was displayed elevated incompleteness motivation and beliefs regarding perfectionism, and low motivation to avoidance harm. The motivational domains of incompleteness and harm avoidance may be related to different levels of beliefs and symptoms. Abstract: Obsessive-compulsive disorder (OCD) is a heterogeneous illness and evidence suggests that different clinical characteristics may relate to varying treatment outcomes. This study was designed to identify subgroups based on core motivational domains in a clinical sample of individuals with OCD, and to compare groups on clinical characteristics. Cluster analyses identified four subgroups including groups with relatively high or low levels of both harm avoidance (HA) and incompleteness (INC) motivations. A subgroup was identified that demonstrated a "traditional profile" marked by high motivation to avoid harm, and elevated levels of beliefs about responsibility/overestimation of threat. The model also contained a subgroup characterized by high incompleteness, low motivation to avoid harm, and higher levels of perfectionistic beliefs and intolerance of uncertainty. Findings reemphasize that current cognitive and behavioral models of OCD may be enhanced by integrating incompleteness/NJREs.